The spin states of cobalt ions and thermo-e.m.f. in erbium and holmium cobaltites - Khirnyi, V.F.; Kozlovskii, A.A.; Semenov, A.V.; Puzikov, V.M. (Functional Materials, 2009)
The temperature dependences of thermo-e.m.f. for Er₁₋ₓSrₓCoO₃₋δ, Ho₁₋ₓSrxCoO₃₋δ, Er₁₋ₓCaxCoO₃₋δ, Ho₁₋ₓCaxCoO₃₋δ ceramics have been studied in the temperature range of 300 K (of 100 K for some materials) to 600 K. The Zeebeck coefficient for Sr doped samples is lowered as the strontium content increases and the temperature rises. It has been shown that the 3d level splitting and the charge disproportionation of cobalt ions is to be taken into account to explain the above-mentioned behavior.